The Effect of Cooperative Learning Models of Stad Type on Class V Science Learning Learning SD - Gingga Prananda; Hadiyanto Hadiyanto (International Journal of Educational Dynamics, 2019)
This study aims to implement cooperative learning model STAD in science teaching fifth grade students of SDN 43 river meadow weaning. This research is an experimental research. The sampling technique used purposive sampling. Instruments in this research is to test student learning outcomes while data analysis techniques using t-test. Based on the results obtained by the average value of the experimental class is 80 and 69.82 in the control class, as seen from the results of the data analysis has been done obtained t (3.286)> t table (1.674), then the hypothesis is accepted. The results of this study are the result of using a model to learn science Student Teams Achievement Division fifth grade students on the cognitive aspects of SDN 43 Sungai Padang Wean.